FUZZY LOGIC MENENTUKAN KEPUASAN MASYARAKAT TERHADAP KINERJA PEGAWAI KECAMTAN DENGAN METODE MAMDANI - Purwanti, Septiana Budi; Ekawati, Nia (LPPM Universitas Putera Batam, 2019)
Employee performance is the level of achievement or work results of a person from the goals that must be achieved or implemented must be in accordance with their respective responsibilities in a certain period of time. Performance satisfaction is the level of one's feelings after comparing the performance or the results he feels compared to his expectations. Sagulung Subdistrict is one of the densely populated sub-districts in Batam city, based on the results of community interviews about the performance of employees in Sagulung sub-district, the results show that the quality of services they receive varies. Hospitality of employees when serving the community is also different between one employee and another employee, besides that community satisfaction with employee performance also varies so that the community's satisfaction with the performance of employees in Sagulung sub-district cannot be concluded. Fuzzy logic using the mamdani method is one method to determine community satisfaction with employee performance in Sagulung sub-district. Based on the results of testing of the data that has been processed, the results of manual calculations are 68.4162 while for the system testing using matlab the results are 68.7. Based on the results of these tests, it can be concluded that fuzzy logic meetode mamdani can be used to determine community satisfaction with employee performance in Sagulung sub-district.